The Corelation Between Team Cohesion and Team Performance in Tourism-Based Organisations - Irina Misoc (Cactus, 2017)
This research focuses on the relationship between team cohesion and team performance in the tourism field.The literature review showed that researchers have found different results on the relationship between these two variables. The present case study was based on the hypothesis that, in the organizations that offer support to their employees, the teams with strong cohesion obtain better results compared with those with poor cohesion. The study was conducted in eight teams that share similar characteristic. The survey method was used for gathering data with two structured questionnaires: one questionnaire used for measuring the performance of the eight teams and another questionnaire used for measuring the team cohesion. The 5 point Likert scale was used to analyze both team performance and team cohesion. As a conclusion, the study revealed that the hypothesis is true, and the strong cohesive teams obtained higher scores in terms of performance, but the relationship between the two variables is more complex and should be studied in detail in future studies.